Corporate social responsibility: opportunity or sophistry? - Pérez Suescún , Leonardo Fabio (Universidad Francisco de Paula Santander, 2015)
This article presents an analysis of corporate social responsibility as an opportunity to materialize the ethical postulates that guide organizational action, based on the theoretical postulates of Argandoña (2009), Bédard (2003), Gómez (2014), Holliday (2010), Ruiz-Navarro (2012), among other authors, and framed in a documentary and analytical methodology. (2014), Holliday (2010), Ruiz-Navarro (2012) among other authors, framed in a documentary and analytical methodology. It discusses the importance of CSR as a valuable tool for the comprehensive management of organizations, adopting principles that allow to comprehensively address the role of the company within society, dimensioning the economic aspects inherent to the organization, but also the social and environmental aspects of the context in which it operates.